Development Of Alkali-Activated Binder Utilizing Silico-Manganese Fume And Blast-Furnace Slag - Nasir, Muhammad (2021)
The negative impacts of proliferation of silico-manganese fume (SiMnF) of about 100-150 kg per tonnage of SiMn alloy produced and increase in the carbon footprint due to production of ordinary Portland cement (OPC) premised the need for this study. This is necessary to enhance public health, minimize the solid waste generation, reduce global warming and develop alternative cost-efficient construction materials for civil engineering infrastructures. This thesis addresses the use of alkali-activated binding technology to mitigate the challenges associated with the concrete and other industries. This led to the development of novel and sustainable alkali-activated mortars (AAMs) using high level of silico-manganese fume (SiMnF) and ground granulated blast furnace slag (GGBFS) as precursor materials (PMs) together with NaOHaq (NH) and Na2SiO3aq (NS) as the alkaline activators (AAs). The optimization of mixes was achieved using L16 orthogonal array based on the Taguchi method (TM). The mix parameters studied were GGBFS/PMs (0-0.5), sand/PMs (1.5-2.4), NH concentration (0-16M), NS/NH ratio (0-3.5), silica modulus (0-3.4) and AAs/PMs (0.5-0.53). The influence of curing methods, namely room-, moist-, and heat-curing (for 3-24 h between 25-95 °C) and durability performance under the exposure to acid and sulphate environments were also studied. Fresh properties and mechanical strength were evaluated, while analytical studies, such as mass stability, bond characteristics, nature of the products formed and morphology of the microstructures were undertaken using thermogravimetric (TG) analysis, FT-IR analysis, X-ray diffraction (XRD) analysis, and scanning electron microscopy (SEM) plus energy dispersive spectroscopy (EDS), respectively. The optimum mortar mix consisted of SiMnF:GGBFS, sand/PMs, Na2SiO3aq/10M-NaOHaq and AAs/PMs ratios of 70:30 wt.%, 1.5, 2.5 and 0.5 such that the SiO2/Na2O, H2O/Na2O and H2O/SiO2 ratios were 1.61, 17.33 and 10.77, respectively. This combination yielded a 3-, 7- and 28-day compressive strength of 22.5, 29.7 and 44.5 MPa, respectively at room-curing, whereas the heat-curing for 6 h at 60 °C was beneficial for attaining the highest strength within 3-days. Among the prominent compounds that defined the microstructure of the developed AAMs were stratlingite/gehlenite hydrate (C-A-S-H), nchwaningite/glaucochroite (C-Mn-S-H), and potassium feldspar (K-A-S-H) phases. Exposing the product to acid attack caused faster deterioration by decalcification and formation of gypsum with S-O bonds and formation of carbonation as a result of reactivity of lime with atmospheric CO2. Exposure to MgSO4aq caused more deterioration leading to spalling of specimens due to formation of gypsum and brucite crystals in comparison with Na2SO4aq where the stability was aided by quartz-based compound. It is envisaged that the results obtained from the novel AAMs would be beneficial in understanding the behaviour and an initiative towards practical application of the materials beside attaining economic, ecological and technical advantages.